2005
DOI: 10.1080/00016480510028492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peri-modiolar cochlear implant positioning on auditory nerve responses: A neural response telemetry study

Abstract: Removal of the stylet had no significant effect on the threshold and growth rate of NRT responses. It caused a reduction in the spread of excitation for electrodes 1, 6 and 20, but not for electrodes 11 and 16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…Based on their observations, the use of a range of stimulus levels may be most appropriate to evaluate electrode interactions. Van Weert et al [12] observed that the spread of excitation in intra-operative NRT measures was larger than that in postoperative measurements. They inferred that this difference related to their high stimulus level in the intra-operative testing procedure.…”
Section: Ecap-derived Excitation Spread Measurement Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on their observations, the use of a range of stimulus levels may be most appropriate to evaluate electrode interactions. Van Weert et al [12] observed that the spread of excitation in intra-operative NRT measures was larger than that in postoperative measurements. They inferred that this difference related to their high stimulus level in the intra-operative testing procedure.…”
Section: Ecap-derived Excitation Spread Measurement Protocolmentioning
confidence: 99%
“…An important goal in the design of cochlear implants is to optimize stimulation strategies or electrode arrays to minimize electrode interactions. In accordance with the hypothesis that an electrode array positioned close to the modiolus will allow more effective and efficient stimulation of the spiral ganglion cells, the Nucleus Contour peri-modiolar electrode array is expected to provide more discrete stimulation and has the potential for better frequency resolution with more selective stimulation of target auditory nerve fibers [11,12] . The purpose of the present study is to verify the difference between the electrode interactions produced by traditional 'straight' and peri-modiolar electrode arrays.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations